Use of Google Sites Learning Media to Improve Students' Cognitive Learning Outcomes Excretory System Material - Mita Nurwita; Hadiansah Hadiansah; Fadli Emsa Zamani (International Journal of Learning Media on Natural Science (IJLENS), 2024)
This study aims to analyze the improvement of students' cognitive learning outcomes in the learning process by using google sites media. The method used in this study is a preexperimental method with the One Group Pretest-Posttest Design model. The sample in this study was class XI IPA in one of the private MA in Bandung with a total of 24 students. The data that has been obtained were analyzed using normality test, paired sample t-test and N-gain test. The results of the data analysis showed that the increase in the N-gain value from the pretest-posttest obtained was 0.67 in the medium category, and the t-count value obtained was -16.353 with a Sig value. (2-tailed) of 0.000. Therefore, the value of Sig. (2-tailed) 0.05, it can be concluded that H_0 is accepted, meaning that there is a significant increase in student cognitive learning outcomes in excretory system learning using google sites media. Based on the results of this study, the use of google sites media has the potential to be used in improving students' cognitive learning outcomes in thelearning process.